QUANTITATIVE ANALYSIS OF INDONESIAN OCEAN WAVE ENERGY POTENTIAL USING OSCILLATING WATER COLUMN ENERGY CONVERTER - Anggraini, Dita; Al Hafiz, Muhammad Ihsan; Derian, Abiyyu Fathin; Alfi, Yofrizal (MATTER: International Journal of Science and Technology, 2015)
Indonesia as a maritime country which is located at 60 N - 110 S latitude and 950– 1410 E longitude has an ocean area reach out 5,000,000 km2. This biggest archipelago country in the world has great ocean energy potential. In the other hand, Indonesian electricity energy demand always increase. Data from Central Bureau of Statistics of Indonesia ( Badan Pusat Statistik) record that in the year 2013, Indonesian electricity consumption achieved 185.9 GWh and it was 234.9 % of Indonesian electricity consumption in 2000. It is indicated by this condition that Indonesia need another alternative energy sources to supply the electricity needs. The ocean energy potential makes Ocean Wave Energy (OWE) precise to be developed in Indonesia. In this paper, study of OWE with Oscillating Water Column (OWC) converter is discussed. Numerical method is used to analyze the quantitative approach of OWE potential in Indonesia. For the calculation, it is assumed that chamber width is 2.5 m and ocean water density is 1030 kg/m3. To calculate the energy, data of ocean significant height from Indonesian Agency for Meteorology, Climatology and Geophysics (BMKG) is used. Power efficiency is assumed to reach 70% and from the numerical calculation, the Indonesian OWE potential distribution can be represented. The greatest power that can be produced is located in Aru Islands and Arafuru Sea, which is reach out 313 kW and has minimum value 55 kW. The median value of ocean power is located in the south coast of Middle Java, Timor Sea, and Banda Sea which have maximum value 198 kW and minimum value 20 kW. This ocean wave energy can be increased by the converter amount and chamber width modification. From the calculation it can be concluded that OWE can be potential alternative energy source in Indonesia.